THE SCIENTIFIC- PHILOSOPHICAL CONCEPT OF READING. - Rakhimov M. A (Scholar Express Journal, 2024)
In this article, it is stated that reading is a complex and multifaceted concept, that reading is a necessary attribute of human spiritual existence as a selforganizing synergistic phenomenon
Keywords: reading; knowledge; information